2003
DOI: 10.1034/j.1600-0714.2003.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of syndecan‐1 down‐regulation and the expression of p53 protein or Ki‐67 antigen in oral leukoplakia with or without epithelial dysplasia

Abstract: Our results reveal that overexpression of p53 protein and Ki-67 antigen, and down-regulation of syndecan-1 expression in the lower part of the epithelium, are associated with dysplastic changes. Therefore, the down-regulation of syndecan-1 expression may be the most important reliable marker for dysplastic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
47
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 38 publications
8
47
2
5
Order By: Relevance
“…Therefore, a genuine reason thus culminated to find out an objective guideline that would attribute collectively and resultantly for an absolutely clear diagnosis. 2 The evaluation of the morphologic profile of the tumor cells is considered to be a determinant factor appropriating the aggressiveness of the tumor. However, at times, the inconspicuous nature of such a profile is found to be inadequate to assign the aggressiveness of the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a genuine reason thus culminated to find out an objective guideline that would attribute collectively and resultantly for an absolutely clear diagnosis. 2 The evaluation of the morphologic profile of the tumor cells is considered to be a determinant factor appropriating the aggressiveness of the tumor. However, at times, the inconspicuous nature of such a profile is found to be inadequate to assign the aggressiveness of the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Kurokawa et al (2003) also found a significant correlation between the down-regulation of syndecan-1 expression and the grade of oral epithelial dysplasia. Down-regulation has also been reported in S C C s o f t h e h e a d a n d n e c k c o m p a r e d t o e x p r e s s i o n i n t h e c o r r e s p o n d i n g n o r m a l epithelium (Soukka et al, 2000), suggesting that syndecan-1 was a useful marker for evaluating pre-malignant lesions of the head and neck region.…”
Section: Syndecan-1 In Oral Cancermentioning
confidence: 72%
“…Many immunohistochemical studies have demonstrated absent or decreased expression of syndecan-1 in many kinds of carcinomas with more aggressive characteristics (Fujiya et al, 2001;Inki et al, 1994;Kumar-Singh et al, 1998;Matsumoto et al, 1997;Stanley et al, 1999;Toyoshima et al, 2001;Wiksten et al, 2000;Wiksten et al, 2001). There are several reports on syndecan-1 expression in head and neck carcinoma (Anttonen et al, 1999;Inki et al, 1994;Kurokawa et al, 2003;Kurokawa et al, 2006;Muramatsu et al, 2008;Ro et al, 2006). However, head and neck carcinoma includes oral, nasal, laryngeal and esophageal carcinomas, and investigation of syndecan-1 expression in oral cancer has been limited.…”
Section: Syndecan-1 In Cancermentioning
confidence: 99%
“…Previous studies have demonstrated that oral leukoplakia and oral squamous cell carcinoma (OSCC) display unique gene expression patterns, including p53 (3)(4)(5), Ki-67 (4,6), and MDM2 (5). Despite the number of studies, the elucidation of reliable prognostic markers for leukoplakia has been unsuccessful.…”
Section: Introductionmentioning
confidence: 99%